Expression of VEGF and Flk-1 and Flt-1 Receptors during Blood-Brain Barrier (BBB) Impairment Following Phoneutria nigriventer Spider Venom Exposure - Monique C. P. Mendonça; Edilene S. Soares; Leila M. Stávale; Catarina Rapôso; Andressa Coope; Evanguedes Kalapothakis; Maria Alice da Cruz-Höfling (Toxins, 2013)
Apart from its angiogenic and vascular permeation activity, the vascular endothelial growth factor (VEGF) has been also reported as a potent neuronal protector. Newborn rats with low VEGF levels develop neuron degeneration, while high levels induce protective mechanisms in several neuropathological conditions. Phoneutria nigriventer spider venom (PNV) disrupts the blood-brain barrier (BBB) and causes neuroinflammation in central neurons along with excitotoxic signals in rats and humans. All these changes are transient. Herein, we examined the expression of VEGF and its receptors, Flt-1 and Flk-1 in the hippocampal neurons following envenomation by PNV. Adult and neonatal rats were evaluated at time limits of 2, 5 and 24 h. Additionally, BBB integrity was assessed by measuring the expression of occludin, β-catenin and laminin and neuron viability was evaluated by NeuN expression. VEGF, Flt-1 and Flk-1 levels increased in PNV-administered rats, concurrently with respective mRNAs. Flt-1 and Flk-1 immunolabeling was nuclear in neurons of hippocampal regions, instead of the VEGF membrane-bound typical location. These changes occurred simultaneously with the transient decreases in BBB-associated proteins and NeuN positivity. Adult rats showed more prominent expressional increases of the VEGF/Flt-1/Flk-1 system and earlier recovery of BBB-related proteins than neonates. We conclude that the reactive expressional changes seen here suggest that VEGF and receptors could have a role in the excitotoxic mechanism of PNV and that such role would be less efficient in neonate rats.